2018
DOI: 10.1159/000490107
|View full text |Cite
|
Sign up to set email alerts
|

Method Used for Tumor Bed Closure (Suture vs. Sealant), Ischemia Time and Duration of Surgery are Independent Predictors of Post-Nephron Sparing Surgery Acute Kidney Injury

Abstract: Introduction: The aim of our study was to examine the influence of tumor complexity and operative variables on the degree and rate of post-nephron sparing surgery (NSS) acute kidney injury (AKI). Methods: We retrospectively reviewed the records of 477 patients who underwent NSS for enhancing renal masses in our institution. AKI was determined using the latest definition by AKIN and RIFLE criteria. Serum creatinine was assessed daily starting from day 1 post-surgery and until discharge (usually on postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Secondly, the improvement of surgeons' skill and surgical technique helped preserve renal function. For example, the durations of renal hilus clamping and surgery were shorter in our patients than in previous studies [8,24,25].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Secondly, the improvement of surgeons' skill and surgical technique helped preserve renal function. For example, the durations of renal hilus clamping and surgery were shorter in our patients than in previous studies [8,24,25].…”
Section: Discussioncontrasting
confidence: 68%
“…Routine circulatory management during partial nephrectomy is to maintain blood pressure change within 20% from baseline and urine output > 0.5 ml/kg/h. However, the incidence of AKI remains high after surgery [8,24,25]. Experience from kidney transplantation suggested that maintaining adequate renal hydration and higher blood pressure after reperfusion (i.e., CVP > 8 mmHg and MAP > 95 mmHg) are bene cial for graft function [14,15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated predictive factors for AKI after PN, which included open and minimally invasive techniques [3,4,12,13,14,15]. Longer WIT and operative duration as well as patient-related factors, such as old age, male sex, obesity, impaired preoperative kidney function, and history of hypertension were identified as risk factors for postoperative AKI [3,4,12,13,14,15,20,21]. In our study, which analyzed risk factors after minimally invasive PN only, WIT >25 min, longer operative duration, and patient-related factors, such as male sex, presence of DM, and high intraoperative urine output were revealed to be independent predictors of postoperative AKI.…”
Section: Discussionmentioning
confidence: 99%
“…WIT is recognized as a strong contributing factor for AKI after PN [3,4,5,12,13,20,21]. WIT >25 min results in irreversible damage that is diffusely distributed throughout the operated kidney, even at six months after PN [25].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the frequency of nephron-sparing surgery is increasing and becoming important. Especially, some previous studies presented that impact of tumor complexity and intraoperative parameters could affect postoperative renal function in patients who underwent nephron sparing surgery [28]. However, in this study, we compared the renal function of single kidney after radical surgery and excluded patients who underwent nephron sparing surgery.…”
Section: Discussionmentioning
confidence: 99%